An Overview Of The Reproductive Health Of Teenage Girl In The Bereng Bengkel Village - Munanadia, Munanadia (Akademi Kebidanan Bunga Husada Samarinda, 2023)
Adolescence is a period of change or transition from childhood to adulthood. WHO defines adolescents as individuals who experience a transitional period gradually reaching sexual maturity. BPS 2022 data estimates that youth in Indonesia is equivalent to 24% of the total population. Healthy adolescents are an investment for the nation's future to meet the demographic bonus in 2030. Young women must be introduced to reproductive health so that adolescents know what is happening to themselves, especially those related to the reproductive organs which are used as determinants of size. a measure of health parameters and used as an indicator of the success or failure of programs to reduce stunting and reduce maternal and infant mortality. This study aims to determine the description of the health of Teenage Girl in the Bereng Bengkel Village. This type of research is descriptive with a quantitative approach. A total of 61 teenage girl aged 10-20 years as a population and the sampling technique was